Antiviral effect of oral antiseptic solutions commonly used in dentistry practice: A scoping review - Eduardo Monteiro Toschi; Luísa Weber Mercado; Sandra Liana Henz (Elsevier, 2023)
Objective: The purpose of this scoping review is to show the evidence available in the literature and provide an overview of the antimicrobial-containing mouthwashes for reducing viral load in order to group the most up-to-date information and make it more accessible to dentists. Design: A structured electronic search in PubMed (Medline), LILACS, EMBASE and EBSCO without temporal restriction was performed. The studies were selected based on their title, abstract and full reading following a pre-established order based on the inclusion and exclusion criteria. The included studies were those that analyzed the effect of viral load reduction by mouthwashes, primary studies, no reviews and in Spanish, English or Portuguese. Results: The search resulted in 1881 articles, at the end of the exclusion of duplicates and selection, 71 articles were included in this scoping review. The substances most commonly found were chlorhexidine (CHX), povidone-iodine (PVP-I), essential oils (EO), cetylpyridinium chloride (CPC), hydrogen peroxide (H2O2) and other substances (OTHERS). Conclusion: Of all the mouthwashes analyzed, the Essential oils, Cetylpyridinium Chloride and Povidone-iodine, showed antiviral potential against common viruses present in the oral cavity, with no significant side effects in short-term use, and are viable options for use as a pre-procedure in clinical routine against SARS-CoV-2 and other types of viruses. The other solutions need further studies to determine their effect and confirm their clinical use.